The Impact of Non-Brazilian Contribution on the Publishing Performance of Psychology Journals in Brazil - Fradkin, Chris (Frontiers in Psychology, 2018)
There is considerable variability in publishing performance among psychology journals in Brazil. However, research as to why is very scarce. This study empirically examined the relationship between non-Brazilian contribution and publishing performance, among these journals. 746 articles from the top-18 psychology journals in Brazil were coded for: study type, international collaboration, and non-Brazilian contribution. Analyses revealed that publishing performance was associated with: (i) international collaboration; and (ii) non-Brazilian contribution. Collaboration with, and contribution from, English-speaking authors was more prevalent among the higher performing journals; while contribution from non-Brazilian Ibero-American authors was more prevalent among the lower performing journals. These findings suggest that publishing performance for psychology journals in Brazil may be strongly tied to non-Brazilian contribution. Implications may be relevant to journal publishers and editors, as well as arbiters of scientific policy.